Cultural Penetration: Post-Modern Threat to Historical Learning - Mareta, Yoan; Rukmana, Lisa; Yaldi, Destri (Indonesian Journal of History Education, 2023)
According to the view of post-modernism in the world of education, humans are no longer subjects and actors to take advantage of science and technology but fall trapped into objects and targets controlled by science and technology as a product of modernism. In fact, technology and information are currently the solution to the development of creativity in the learning process which is also reflected in the implementation of the independent learning curriculum. This research uses a qualitative paradigm with a literature study method. In-depth analysis of the process of elaboration and subjective meaning are the thing that is most highlighted in qualitative research. The theory is then used as a guide to align the research focus with the facts of the field. The research results obtained are described as follows: Post-Modern Threats, Cultural penetration in the historical learning, and Digitalization and historical empathy. The conclusion is that digitization in historical learning is an important literacy process and really requires technological advances. But furthermore, the packaging must still include the essence of the nation's values and character.